Understanding Virtual MSME Product Marketing Strategy: A Study of Management and Business Economics - Julinta Paulina; Pilifus Junianto; Imam Fauzan; Sukma Irdiana; Dendy Eta Mirlana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Running a business in the modern era is different from business in the past. Advanced businesses are those that can market their products and services technologically. This study aims to gain a detailed understanding of the virtual marketing strategy of MSME products. For this reason, we have obtained evidence that we have examined from various sources, including scientific papers, especially technological marketing strategies for small business products. The win was under a phenomenological approach, collecting as much data as possible to extract the essence to answer the current problem. Incoming studies include coding the theme data, evaluating information, drawing conclusions, and looking for valid s in the pan in answering the problem. Based on the analyzed data plus the discussion, we can conclude that online marketing is successful by following the appropriate steps for digital media, mapping out marketing, selecting suitable digital media, and implementing all internet-based marketing activities. Thus, it is hoped that the findings of this study will help improve the quality of future studies.